Content Analysis Of Textbook Evaluation: Assessing Everyday English For Hospitality Professionals - Abdul Syahid; Devi Hanastasya; Shifa Soraya Lestari; Wilda Cahyani; Ahmad Basahil (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This study conducts a comprehensive content analysis of the textbook titled "Everyday English for Hospitality Professionals". Through the lens of textbook evaluation, the research aims to assess the effectiveness and suitability of the content in meeting the learning needs of professionals in the hospitality industry. Utilizing established criteria, the analysis scrutinizes the relevance, clarity, and practicality of the material, particularly in facilitating language skill development tailored to the demands of the hospitality profession. The findings of this study offer valuable insights for curriculum development and instructional material selection, contributing to the enhancement of English language learning experiences for hospitality professionals.